Nonlinear correlation and mediation effects between serum 25-hydroxyvitamin D levels and all-cause mortality in COPD patients - Jiang, Qi; Jiang, Yuewen; Ma, Zheru; Huang, Jingda; Li, Yang (Frontiers in Nutrition, 2024)
Background: Numerous studies have shown that low levels of vitamin D are linked to a higher risk of inflammatory diseases and their progression. However, how vitamin D levels affect mortality in chronic obstructive pulmonary disease (COPD) patients is still unclear. Thus, this study aimed to explore the relationship between serum 25-hydroxyvitamin D [25(OH)D] levels and the risk of death from all causes in U.S. adults with COPD. Methods: This study analyzed 1,876 adults with COPD from the National Health and Nutrition Examination Survey (2005-2018). Mortality data up to December 31, 2019, were obtained from the National Death Index (NDI) records. Participants were categorized into three groups according to their 25(OH)D levels: Q1 (<50.0 nmol/L) for deficiency; Q2 (50.0-74.9 nmol/L) for insufficiency; and Q3 (≥75.0 nmol/L) for adequacy. A weighted Cox regression model assessed the link between 25(OH)D levels and mortality. Kaplan-Meier survival curves, subgroup, and sensitivity analyses were conducted. Additionally, the relationship between 25(OH)D and the hazard ratio (HR) was detailed through restricted cubic spline analysis. Mediation analysis revealed how 25(OH)D mediates the relationship between Dietary Inflammatory Index and mortality. Results: There were 395 all-cause deaths during the follow-up, resulting in a mortality rate of 21.06%. After adjusting for potential confounders, higher 25(OH)D levels significantly correlated with a lower risk of all-cause mortality in COPD patients (HR=0.52, 95% CI: 0.37-0.72, p<0.001). Restricted cubic spline analysis indicated a non-linear relationship between 25(OH)D levels and all-cause mortality (p for nonlinear=0.023), with levels below 63.4 nmol/L posing an independent risk for all-cause mortality in COPD patients (HR=0.98, 95% CI: 0.97-0.99, p=0.005). Sensitivity and subgroup analyses confirmed our results' robustness, with mediation analysis showing 25(OH)D's 22% mediating effect on diet-induced inflammation and all-cause mortality in COPD patients. Conclusions: 25(OH)D independently lowers the risk of all-cause mortality in COPD patients, with a non-linear L-shaped correlation, and mediates the effect of Dietary Inflammatory Index on mortality, suggesting new therapeutic possibilities.